α-Glycerol monolaurate promotes tight junction proteins expression through PKC/MAPK/ATF-2 signaling pathway - Dai, Siyu; Li, Cunjie; Li, Dagang; Wang, Hong (Frontiers in Nutrition, 2025)
IntroductionThis study investigates the effects of α-GML on intestinal epithelial tight junction (TJ) protein expression and its molecular mechanisms. Recognizing the critical role of TJ proteins in intestinal barrier function and the potential of α-GML to enhance this barrier, we employ the IPEC-J2 cell model. Our aim is to validate the regulatory impact ofα-GML on TJ protein expression and elucidate the underlying signaling pathways, thereby offering new strategies for intestinal health maintenance.MethodsUtilized Data-Independent Acquisition (DIA) analysis to identify optimal targets of α-GML in modulating Tight Junction (TJ) protein expression. Treated cells with specific inhibitors of PKC and MAPK to assess their role in TJ regulation by α-GML. Co-treated cells with the MAPK inhibitor SCH772984 and α-GML to study the effects on p-ATF-2 expression. Evaluated the effects of SCH772984 and ATF-2 overexpression on the protein expression levels of phosphorylated ATF-2, ZO-1, and OCLN.ResultsRevealed that α-GML’s modulation of TJ proteins might involve the PKC/MAPK signaling pathway, leading to ATF-2 phosphorylation. Both PKC and MAPK inhibitors reduced TJ protein expression (p < 0.05, p < 0.01 or p < 0.001), indicating their involvement in α-GML’s regulation. SCH772984 counteracted α-GML-induced upregulation of p-ATF-2 (p < 0.05), suggesting MAPK’s role in this process. Identified potential ATF-2 binding sites on ZO-1 and OCLN promoters. ATF-2 significantly enhanced ZO-1 promoter activity (p < 0.001). SCH772984 reduced phosphorylated ATF-2, ZO-1, and OCLN levels (p < 0.05 or p < 0.01), while ATF-2 overexpression rescued this decrease (p < 0.05 or p < 0.01), confirming ATF-2’s role in TJ protein upregulation via the MAPK pathway.DiscussionOur study indicated that α-GML enhanced the expression of TJ proteins through the PKC/MAPK/ATF-2 pathway, thereby enhancing the barrier function of intestinal epithelial cells.